2021
DOI: 10.1038/s41385-020-00348-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-22 receptor signaling in Paneth cells is critical for their maturation, microbiota colonization, Th17-related immune responses, and anti-Salmonella immunity

Abstract: Interleukin-22 (IL-22) signaling in the intestines is critical for promoting tissue-protective functions. However, since a diverse array of cell types (absorptive and secretory epithelium as well as stem cells) express IL-22Ra1, a receptor for IL-22, it has been difficult to determine what cell type(s) specifically respond to IL-22 to mediate intestinal mucosal host defense. Here, we report that IL-22 signaling in the small intestine is positively correlated with Paneth cell differentiation programs. Our Il22R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 48 publications
(120 reference statements)
1
43
0
Order By: Relevance
“…Our study also found that L.lactis increased the jejunal gene expression of IL-18 and IL-22 and reduced the ileal gene expression of IL-22. IL-18 can induce the intestinal epithelium to produce antimicrobial proteins ( 37 ), while, intestinal IL-22 signaling was positively correlated with the differentiation and antimicrobial effect of Paneth cells ( 38 ), and IL-22 has been reported to promote intestinal stem cell-mediated epithelial regeneration ( 39 ). Thus, L.lactis transplantation regulates intestinal immune response, which would help maintain intestinal immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that L.lactis increased the jejunal gene expression of IL-18 and IL-22 and reduced the ileal gene expression of IL-22. IL-18 can induce the intestinal epithelium to produce antimicrobial proteins ( 37 ), while, intestinal IL-22 signaling was positively correlated with the differentiation and antimicrobial effect of Paneth cells ( 38 ), and IL-22 has been reported to promote intestinal stem cell-mediated epithelial regeneration ( 39 ). Thus, L.lactis transplantation regulates intestinal immune response, which would help maintain intestinal immune homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroglial identifier gene lists were generated taking advantage of the newly available single-cell RNA sequencing datasets from the enteric nervous system (SCP1038 [ 10 ], SRP135960 [ 12 ]), intestinal epithelial and stromal cells (GSE92332 [ 24 ], SCP259 [ 25 ]), as well as bulk RNA sequencing datasets from isolated intestinal epithelial organoids (GSE148727 [ 26 ], GSE159423 [ 27 ]). Genes with a specific expression in the enteric neuroglial datasets but not the other datasets including epithelial and stromal were chosen to create the list.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the localization of paneth cells at the crypt bottom exposes them to an environment that was suggested by computational modeling to be characterized by particularly high ILC3-derived IL-22 levels (95). Together with the recently shown importance of IL-22 signaling for paneth cell differentiation and effector functions (104), this predisposes ILC3s as potential regulators of paneth cells. Future research will help to clarify the biological relevance of these suggested ILC-IEC interactions in IBD.…”
Section: Further Iec Subtypes-ilcsmentioning
confidence: 98%